Internet gaming experience among adolescents in Metro Manila: A case study - Palackal, George (Animo Repository, 2015)
This study explored the experience of internet gaming disorder (IGD) among adolescents in a high school in Metro Manila. It aimed to understand the antecedents, symptoms and consequences of IGD. The respondents of the study consisted of 8 adolescents with IGD and 8 highly engaged adolescent gamers. This paper used multiple case study research design. Responses from the participants revealed four major themes namely: a) experience of internet gaming, b) risk factors in developing IGD, c) warning signs of IGD, and d) ramifications of IGD. IGD experience includes cognitive, affective, physiological and behavioral reactions. Risk factors in developing IGD involve excessive gaming, escapism and coping, entertainment and peer recognition. Pre-occupation with gaming, inability to control the urge to play and lie/deception about gaming are warning signs of IGD while having relational conflicts caused by gaming and declining of grades are ramifications of IGD. Parental control over gaming serves as protective factors for the highly engaged gamers. Implications for counseling practice are discussed. Keywords: internet gaming disorder, internet gaming, counseling, Filipino adolescents